Dimensionality and Measurement Invariance of the State-Trait Inventory for Cognitive and Somatic Anxiety (STICSA) and Validity Comparison With Measures of Negative Emotionality - Tindall, Isabeau K.; Curtis, Guy J.; Locke, Vance (Frontiers in Psychology, 2021)
This study explored the factor structure of the State-Trait Inventory for Cognitive and Somatic Anxiety (STICSA) and measurement invariance between genders. We also measured concurrent and divergent validity of the STICSA as compared to the State-Trait Anxiety Inventory (STAI). A sample of 1064 (N Females = 855) participants completed questionnaires, including measures of anxiety, depression, stress, positive and negative affect. Confirmatory factor analyses supported the original factor structure of the STICSA, which was invariant between genders. Overall, the STICSA had superior concurrent and divergent validity as compared to the STAI. The somatic subscales were also significantly less correlated with depression, and positive and negative affect. Further, the somatic, as compared to cognitive anxiety STICSA subscales were less correlated with depression. This suggests that the STICSA, especially the somatic anxiety subscales, might hold the key to distinguishing between different types of anxiety, as well as between anxiety and depression.